The Hiding Hand: A Rejoinder to Flyvbjerg on Hirschman. (March 2018) - Room, Graham
Highlights: Challenges Flyvbjerg's recent critique of Hirschman's "Hiding Hand" ( World Development Vol 84, pp 176–189). Shows, by taking account of Hirschman's scholarship more broadly, that much of his approach to the "Hiding Hand" remains valuable. Highlights the research agenda that the "Hiding Hand" opens up. Summary: In a recent article in World Development, Flyvbjerg confronted Hirschman's principle of the "Hiding Hand" and "providential" or "beneficial ignorance" ( World Development Vol 84, pp 176–189). This states that development projects typically incur major cost overruns and other implementation problems, which put in question the decision to launch them in the first place. Indeed, had these difficulties been known in advance, the projects might never have been tried. Flyvbjerg challenges the empirical validity of this principle and the sloppiness of Hirschman's own argument. This rejoinder, while accepting that Hirschman presents his argument less than well, argues that Flyvbjerg is too quick to dismiss it, and that by taking account of Hirschman's scholarship more broadly, much of his approach remains valuable.